Herpes simplex virus and varicella-zoster virus helicase-primase inhibitors - Field, Hugh J. (Henry Stewart Talks, 2011)
Herpesvirus infections in man, Diseases caused by alphaherpesvirus, HSV and VZV, Immunocompromised hosts, Infection, latency and reactivation, Morphology of herpesvirus virion, Productive replication cycle, The herpesvirus genome, HSV and VZV antiviral therapy, Nucleoside analogue therapy, Historical prospective, Genes coding for proteins targeted by antivirals, Inhibitors of DNA synthesis, A new target, HSV helicase-primase complex, Clinical potential of Helicase primase inhibitors (HPIs), Studying HPI in vivo, Antiviral efficacy, Dose response, The effects of HPI on HSV latency, The development of HPI antiviral drug resistance, HPI resistant mutants growth and pathogenicity